2013
DOI: 10.3758/s13423-013-0431-2
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional overlap between time and space

Abstract: Several pieces of evidence suggest that our mental representations of time and space are linked. However, the extent of this linkage between the two domains has not yet been assessed. We present the results of two experiments that draw on the predictions of the dimensional overlap model (Kornblum, Hasbroucq, & Osman, Psychological Review 97:253-270, 1990). The stimulus and response sets in these reaction time experiments were related to either time or space. The obtained stimulus-response congruency effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…There was no main effect of Temporal Reference, min F′(1,30) = 0.16, p = .69. Consistent with previous studies (Eikmeier et al, 2013;Sell & Kaschak, 2011;Torralbo et al, 2006;Ulrich et al, 2012), an interaction of Temporal Reference and Response Alternative emerged, min F′(1,54) = 67.46, p b .001, reflecting a space-time congruency effect. Most crucially, however, this interaction was not significantly modulated by Response Mode, min F′(1,45) = 0.46, p = .50.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…There was no main effect of Temporal Reference, min F′(1,30) = 0.16, p = .69. Consistent with previous studies (Eikmeier et al, 2013;Sell & Kaschak, 2011;Torralbo et al, 2006;Ulrich et al, 2012), an interaction of Temporal Reference and Response Alternative emerged, min F′(1,54) = 67.46, p b .001, reflecting a space-time congruency effect. Most crucially, however, this interaction was not significantly modulated by Response Mode, min F′(1,45) = 0.46, p = .50.…”
Section: Resultssupporting
confidence: 89%
“…Empirical evidence suggests that this congruency effect is consistent with a strong conceptual overlap between time and space (Eikmeier et al, 2013). Yet, to our knowledge, no study had directly addressed the question of whether the spatial characteristics of the response modulate the size of the space-time congruency effect.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our common understanding of time as a one-dimensional, unidirectional, dense flow is thus derived from our richer conception of the three-dimensional space according to this view. Many findings concerning time in language and cognition lend support to this view (e.g., Boroditsky, 2000;Boroditsky & Ramscar, 2002;Casasanto & Boroditsky, 2008;Clark, 1973;Eikmeier, Schröter, Maienborn, Alex-Ruf, & Ulrich, 2013;Evans, 2006;Haspelmath, 1997;Moore, 2006;Traugott, 1975). Yet, beyond this general assumption, many details of such a mapping from space to time, its implementation, its scope and its implications for the representation and processing of temporal information still remain unresolved.…”
Section: Introductionmentioning
confidence: 81%
“…Previous experimental studies have shown that people code deictic time in terms of a mental timeline which typically runs from left to right or from back to front (e.g., Eikmeier et al, 2013;Ouellet et al, 2010;Santiago et al, 2007;Torralbo et al, 2006;Ulrich & Maienborn, 2010;Ulrich et al, 2012). Furthermore, these studies have demonstrated that an activation of the mental timeline can be triggered by lexical expressions and grammatical means which refer explicitly to the past or to the future, i.e.…”
Section: Discussionmentioning
confidence: 96%